Clinical features of endobronchial tuberculosis - Samardžić, Natalija; Jovanović, Dragana; Marković-Denić, Ljiljana; Roksandić - Milenković, Marina; Popević, Spasoje; Škodrić-Trifunović, Vesna (Vojnosanitetski pregled, 2014)
Background/Aim. Endobronchial tuberculosis (EBTB) is a specific type of pulmonary tuberculosis which often affect the tracheobronchial tree, and can be microbiologically and/or pathohistologically confirmed. The aim of the study was to determine the clinical features and diagnostic aspects of EBTB. Methods. This retrospective study was conducted at the Clinic for Lung Diseases, Clinical Center of Serbia, Belgrade, from January 1997 to December 2007. All patients with EBTB confirmed by bronchoscopy with biopsy during a study period were analysed. Data included the patient’s medical history, a physical exam, chest X-ray, mycobacterial analysis of sputum samples, endoscopic types and patohistological confirmation. Results. In the study, 57.6% of the patients were males. The most frequent symptoms were cough (71.2%), malaise (54.2%), fever (49.2%), weight loss (40.7%), and hemoptysis (13.6%). Most of the patients were diagnosed within 30 days of symptoms onset. Sputum examination showed acid-fast bacilli in 31.4% of the patients, while sputum culture for tuberculosis bacilli were positive in 55.9% of the patients. The most common radiographic localization was in the upper lung lobes (63.5%). Cavities were present in 60.4% of the patients. The most common endoscopic subtype determined by bronchoscopy were nonspecific bronchitis (39.9%) and edematous-hyperemic subtype (36.4%). Conclusion. EBTB was more frequent among men, and  among people in their fifties in our country. Detailed bronchoscopic examination, correlated with clinical and laboratory findings, will improve diagnostic rate and provide timely therapy.
Keywords: tuberculosis; pulmonary; diagnosis; signs and symptoms; radiography; bronhoscopy; histological techniques